2015
DOI: 10.1016/j.canlet.2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic reprogramming supports the invasive phenotype in malignant melanoma

Abstract: Invasiveness is a hallmark of aggressive cancer like malignant melanoma, and factors involved in acquisition or maintenance of an invasive phenotype are attractive targets for therapy. We investigated melanoma phenotype modulation induced by the metastasis-promoting microenvironmental protein S100A4, focusing on the relationship between enhanced cellular motility, dedifferentiation and metabolic changes. In poorly motile, well-differentiated Melmet 5 cells, S100A4 stimulated migration, invasion and simultaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 45 publications
1
69
1
Order By: Relevance
“…As a result, the increased expression of these proteins in metastatic samples suggests a metabolic remodeling toward a hyperglycolytic and acid-resistant phenotype in the progression to an invasive phenotype, which is in accordance with evidence obtained from different approaches. 29 In the case of CAIX, a significant increase was observed in 2 transitions along melanoma progression: from benign nevi to primary tumor and from lymph-node metastasis to distant metastases. CAIX is a HIF-1a-induced pH regulator that contributes to the acid-mediated cancer cell invasive phenotype, [37][38][39][40] and has been associated with poor prognosis in a variety of neoplasias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, the increased expression of these proteins in metastatic samples suggests a metabolic remodeling toward a hyperglycolytic and acid-resistant phenotype in the progression to an invasive phenotype, which is in accordance with evidence obtained from different approaches. 29 In the case of CAIX, a significant increase was observed in 2 transitions along melanoma progression: from benign nevi to primary tumor and from lymph-node metastasis to distant metastases. CAIX is a HIF-1a-induced pH regulator that contributes to the acid-mediated cancer cell invasive phenotype, [37][38][39][40] and has been associated with poor prognosis in a variety of neoplasias.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26] Meanwhile, additional studies, both in human samples and in vitro models, have shown that melanoma cells exhibit the Warburg effect 27,28 and that the progression to an invasive phenotype occurs under a metabolic switch from mitochondrial oxidative phosphorylation to glycolytic flux followed by lactate production. 29 As a result, melanoma cell metabolism has been pointed out as a promising strategy for melanoma treatment. [29][30][31] Although the interest in the metabolic reprogramming of cancer cells is arising in the last years, 2 few studies focus on the metabolic profile of melanoma cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact reasons behind the metabolic switch are not known, but likely reasons include: (i) sustaining high proliferative rates in hypoxia [27] and (ii) evading apoptosis as a result of reduced mitochondrial function [28]. Increases in glycolysis have been linked to invasiveness, with changes in glycolysis identified in several studies [29,30]. However, in all studies listed above, cancer cells were grown on cell culture media containing high levels of glucose between 10 and 25 mM.…”
Section: Cancer Hallmarks and Metabolic Reprogrammingmentioning
confidence: 99%
“…Together, this suggests that both direct and indirect interactions with the microenvironment foster colonization of metastatic melanoma in the brain. Exposure of melanoma cells to the micro-environmental factor S100A4 causes a Warburg-like shift in metabolism, which promotes an invasive, malignant phenotype (62). In addition, metastatic melanoma cells exhibit increased oxidative phosphorylation, glutaminolysis, and β-oxidation compared to non-metastatic cells (63).…”
Section: Melanoma-to-brain Metastasesmentioning
confidence: 99%